The Role Of Video Games In Teaching English - Ruzieva Mukhayyo; Nomozova Marg'uba Allonovna (Open Academia, 2024)
This article delves into the innovative integration of video games into English language education, exploring their role in creating an interactive learning environment. Highlighting the advantages, the article discusses how video games enhance vocabulary, grammar, and cultural exposure. The immediate feedback mechanism and progress tracking features are examined, emphasizing their impact on effective language learning. The article also underlines the motivational aspect, illustrating how video games keep learners engaged and committed to the language acquisition process. As education evolves, understanding the pedagogical potential of video games becomes crucial, presenting a promising avenue for a dynamic and enjoyable English language learning experience
Keywords: English language learning; interactive learning; vocabulary enhancement